2022
DOI: 10.3390/jcm11061669
|View full text |Cite
|
Sign up to set email alerts
|

Patients Hospitalized for Ischemic Stroke and Intracerebral Hemorrhage in France: Time Trends (2008–2019), In-Hospital Outcomes, Age and Sex Differences

Abstract: Background: Rates of patients hospitalized for stroke increased among people aged under 65 years in France, as has been found in other countries. Methods: To analyze time trends in the rates of patients hospitalized for ischemic stroke (IS) and intracerebral hemorrhage (ICH) in France between 2008 and 2019 and determine related short-term outcomes mainly, we selected all patients hospitalized for stroke using the French national hospital database. Results: The average annual percentage change in the rates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In terms of sex, some studies did not identify sex differences (Carcel et al., 2019 ) or age‐sex interaction effects (James et al., 2017 ) on mortality after ICH, while others found a higher mortality rate in females (Ganti et al., 2013 ; Nilsson et al., 2002 ; Purroy et al., 2019 ). In contrast, some studies have observed a lower mortality rate in females, especially in young and middle‐aged females after cross‐age grouping (Ayala et al., 2002 ; Bushnell et al., 2014 ; Olie et al., 2022 ; Sheikh & Bullock, 2007 ; Shigematsu et al., 2015 ; Umeano et al., 2013 ; Zia et al., 2009 ), which is similar to our findings. The reasons for these differences may be related to the different study types (retrospective vs. prospective), study populations (geographical vs. ethnic), inclusion criteria, analysis methods, and follow‐up evaluation methods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of sex, some studies did not identify sex differences (Carcel et al., 2019 ) or age‐sex interaction effects (James et al., 2017 ) on mortality after ICH, while others found a higher mortality rate in females (Ganti et al., 2013 ; Nilsson et al., 2002 ; Purroy et al., 2019 ). In contrast, some studies have observed a lower mortality rate in females, especially in young and middle‐aged females after cross‐age grouping (Ayala et al., 2002 ; Bushnell et al., 2014 ; Olie et al., 2022 ; Sheikh & Bullock, 2007 ; Shigematsu et al., 2015 ; Umeano et al., 2013 ; Zia et al., 2009 ), which is similar to our findings. The reasons for these differences may be related to the different study types (retrospective vs. prospective), study populations (geographical vs. ethnic), inclusion criteria, analysis methods, and follow‐up evaluation methods.…”
Section: Discussionsupporting
confidence: 90%
“…Management of ICH needs to be based on sex differences to avoid misunderstandings and bias (The Lancet Network, 2019 ). There are previous contradictions regarding sex differences and mortality after ICH (Ayala et al., 2002 ; Bushnell et al., 2014 ; Carcel et al., 2019 ; Ganti et al., 2013 ; Nilsson et al., 2002 ; Purroy et al., 2019 ; Shigematsu et al., 2015 ; Sheikh & Bullock et al., 2007 ; Umeano et al., 2013 ; Zia et al., 2009 ). This may be due to the fact that aging affects the release of systemic substances in people of the same sex, affecting clinical recovery after ICH (Engman et al., 2012 ; Guevara et al., 2011 ; Hsieh et al., 2016 ; Lei et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of five randomized controlled trials found that women were more likely to be admitted to an acute stroke unit [13], whereas other studies TA B L E 1 Overall and sex-specific unadjusted baseline characteristics of the population. from France and Canada did not confirm significant sex disparities in rates of stroke unit admission [14] or showed the contrary [15].…”
Section: Discussionmentioning
confidence: 81%
“…Reassuringly, such differences seem to decrease toward more sex equity over time; a recent nationwide analysis in the United States showed that in the past decade, utilization of rt‐PA increased at a faster pace in women compared to men [34]. This trend was confirmed by epidemiological data from France [15] and by the aforementioned meta‐analysis by Strong and coworkers [33]. Recent data from Catalonia for the period from 2016 to 2019 showed even a higher proportion of acute reperfusion therapies in women [24].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation